Electrification as a development and sustainability approach in rural areas using renewable energy sources (2024)
BACKGROUND AND OBJECTIVES: Within the Colombian Caribbean region, a number of rural communities utilize self-generated energy as a result of their limited access to the national electricity network. This energy generated is achieved through a combination of combustion engines and renewable sources. However, certain communities face challenges maintaining daily energy autonomy, resulting in developmental disparities. Consequently, the study seeks to create a method for evaluating the accessibility of renewable resources and performing risk assessments to facilitate the introduction of electrification projects in rural regions of the Colombian Caribbean. METHODS: A review was made of the feasibility of financing projects with a focus on renewable energies by government financing entities in Colombia. Subsequently, risk mitigation strategies were utilized in projects of this kind, analyzing the available renewable resources in the locality such as wind and photovoltaic solar energy. FINDINGS: The main factor impeding the success of renewable energy projects in the Colombian Caribbean is political risk. Despite the region’s significant solar and wind energy potential, as demonstrated by statistical analyses based on meteorological data, these projects frequently struggle to achieve optimal operational outcomes due to political instability. Presenting potential solar radiation levels ranging from 5 kilowatt-hours per square meter per day, and wind speeds exceeding 2 and 7 meters per second in certain localities. The aforementioned statement suggests that the projects that have been signed are backed by insufficient dimensioning. CONCLUSION: The strategies devised for effective administration of energy supply to these communities are outlined, taking into account the assessment of wind and solar energy capacities specific to each area, as well as the identification of potential political and financial risks which pose the most significant uncertainties for such initiatives. The solar radiation assessments obtained are conducive to accurately sizing photovoltaic systems, while the identified wind speeds indicate a need to reevaluate methods for harnessing these wind resources efficiently